The Effect of the Jigsaw Technique on Academic Achievement in Geography Education - Engin, Fahrettin; Sengün, Mustafa Taner; Turan, Cihat (My University, 2025)
The renewed geography curriculum emphasizes a student-centered approach in which teachers act as guides while students actively construct knowledge through experiential learning. This study investigates the effect of the Jigsaw cooperative learning technique on student achievement in geography. A pre-test–post-test control group experimental design was employed. An achievement test covering the “Natural Systems” unit of the 9th-grade geography curriculum was developed and administered as both the pre-test and post-test. The experimental group received instruction using the Jigsaw technique, while the control group was taught through traditional methods. The study was conducted with 58 9th-grade students (32 boys and 26 girls) enrolled in a public high school in central Elazığ, where class placements are random and include students with varying academic performance levels. Due to student attrition in the control group, the experimental group consisted of 34 students and the control group 24 students. Data analyses were conducted using SPSS. Descriptive statistics and independent and paired samples t-tests were applied to compare the pre-test and posttest scores. The findings revealed significant differences between the pre-test and post-test scores within and between groups. Overall, participation in the Jigsaw-based instruction produced a statistically significant improvement in students’ geography achievement compared to traditional teaching. These results indicate that cooperative learning is more effective than conventional methods in enhancing student learning outcomes.
Keywords: Geography; Collaborative learning; Jigsaw; interactive learning; peer learning